Anionic N18 Macrocycles and a Polynitrogen Double Helix in Novel Yttrium Polynitrides YN6 and Y2N11 at 100 GPa. Issue 34 (13th July 2022) - Aslandukov, Andrey; Trybel, Florian; Aslandukova, Alena; Laniel, Dominique; Fedotenko, Timofey; Khandarkhaeva, Saiana; Aprilis, Georgios; Giacobbe, Carlotta; Lawrence Bright, Eleanor; Abrikosov, Igor A.; Dubrovinsky, Leonid; Dubrovinskaia, Natalia
Abstract: Two novel yttrium nitrides, YN6 and Y2 N11, were synthesized by direct reaction between yttrium and nitrogen at 100 GPa and 3000 K in a laser‐heated diamond anvil cell. High‐pressure synchrotron single‐crystal X‐ray diffraction revealed that the crystal structures of YN6 and Y2 N11 feature a unique organization of nitrogen atoms—a previously unknown anionic N18 macrocycle and a polynitrogen double helix, respectively. Density functional theory calculations, confirming the dynamical stability of the YN6 and Y2 N11 compounds, show an anion‐driven metallicity, explaining the unusual bond orders in the polynitrogen units. As the charge state of the polynitrogen double helix in Y2 N11 is different from that previously found in Hf2 N11 and because N18 macrocycles have never been predicted or observed, their discovery significantly extends the chemistry of polynitrides. Abstract : The reaction between yttrium and molecular nitrogen at 100 GPa under laser heating at 3000 K yields two novel compounds, YN6 and Y2 N11 . Their crystal structures feature a unique organization of nitrogen atoms: an anionic N18 macrocycle and a polynitrogen double helix, respectively.